Using the coaches voice to improve the representation and experience of females in coaching: a Gaelic games perspective - T. Haughey; A. Graffin; P. Donnelly; B. McGrane; P. McGourty; N. Stapleton; A. Moore; N. Williams; W. Harmon; P. Horgan; A. Lane (Frontiers Media S.A., 2024)
BackgroundFemale coaches across all sports and levels are underrepresented on a global scale, existing as peripheral figures on the coaching landscape. This is evident in an Irish context, with a recent report suggesting that just 18.7% of coaches in Gaelic games are female. The reasons for lower levels of female involvement in coaching have been widely documented, and include females feeling undervalued or under-appreciated, lacking confidence, and experiencing a lack of respect, gender stigmatism, and unconscious bias, within unsupportive organisational cultures. The purpose of this research was to examine the impact of structural and cultural factors on female coaches' lived experiences of coaching in Gaelic games.MethodsFollowing ethical approval, 8 online semi-structured focus groups with 38 female coaches from 5 cohorts; generic, inactive, fulltime paid, coach developers, and cross code coaches were conducted. The data were analysed using thematic analysis. Following transcription, codes and quotes relevant to the main research questions in the study were collated and assessed with reference to the Ecological Intersectional Model.DiscussionThrough an iterative process of analysis and interpretation, four key themes, and 13 sub themes were constructed, shaped, and reshaped by the research team. These reflected personal factors, coaching contexts, organisational supports and societal influences that impacted on the lived experiences of female coaches in Gaelic games. These included many barriers and challenges experienced personally and within the organisational culture of Gaelic games that inhibit female involvement and full engagement across the coaching pathway. Leaders within Gaelic games should consider mentorship and networking; development of holistic coaching environments; and greater flexibility in coach education to increase and retain representation of females in coaching.